Diversity of Contents in Dhrubesh Chandra Regmi’s Music, Myth and Melody: A Brief History of Nepali Music - Sharma, Yam Prasad (Journal of Fine Arts Campus, 2024)
Prof. Dr. Dhrubesh Chandra Regmi’s book Music, Myth and Melody: A Brief History of Nepali Music presents the history of Nepali music in concise form analyzing multiple genres of music including classical, spiritual, folk, ethnic, modern and contemporary music, compositions and instruments. The work traces the roots of Nepali music along with the evolution and development. Professor Regmi emphasizes the significance of classical music in composition of aesthetic forms in contemporary times. Time, place and context affect the development of art. Socio-political and economic condition of the country is closely connected to the creation of art. Royal patronage helped in the institutionalization and development of Nepali music. The blend of classical and native folk music has given unique identity to Nepali music. The book introduces most of the dynamics and genres of the music and indicates the directions for further exploration and research. The coherence, clarity and conciseness in presentation makes the reading experience rich. The book is equally useful to the music students, teachers, researchers and general readers as well.